The Effect of Lifestyle on Purchasing Decision of Salad in Pekanbaru City - Fitri, Mutiara (Indonesian Journal of Economics, Social, and Humanities, 2024)
An individual with a healthy lifestyle will tend to consume foods that are good for health such as salads. Lifestyle is a factor that can affect people in making decisions to buy food. This research aims to analyze the effect of lifestyle on purchasing decisions for salad in Pekanbaru City. Respondents in this research were people who lived in Pekanbaru City, consumed salad, and were 17-65 years old. The consumer survey was carried out in July 2022. The results of research through SEM-PLS showed that the factors that affected the purchase of salads in Pekanbaru City were lifestyle, level of education, product quality, gender, and income as indirect effects through lifestyle. Based on the research results, the policy implications were (1) producers must pay more attention to the target market; (2) producers can reach middle to lower-income consumers by making products with lower selling prices or promotions; (3) producers must attract male consumers to consume more salads; (4) the government conducts education to adopt a healthy lifestyle for individuals with low levels of education, and (5) producers must improve product quality.